New putative periodontopathogens and periodontal health‐associated species: A systematic review and meta‐analysis - Antezack, Angéline; Etchecopar‐Etchart, Damien; La Scola, Bernard; Monnet‐Corti, Virginie (Journal of periodontal research, 2023)
To investigate the existence of any association between new putative periodontal pathogens and periodontitis. Two independent reviewers conducted electronic literature searches in the MEDLINE (PubMed), EMBASE, DOSS and Google Scholar databases as well as a manual search to identify eligible clinical studies prior to November 2022. Studies comparing the prevalence of microorganisms other than the already‐known periodontal pathogens in subgingival plaque and/or saliva samples between subjects with periodontitis and subject with periodontal health were included. Meta‐analyses were performed on data provided by the included studies. Fifty studies including a total of 2739 periodontitis subjects and 1747 subjects with periodontal health were included. The Archaea domain and 25 bacterial species ( Anaeroglobus geminatus , Bacteroidales [G‐2] bacterium HMT 274, Desulfobulbus sp. HMT 041, Dialister invisus , Dialister pneumosintes, Eubacterium brachy , Enterococcus faecalis, Eubacterium nodatum , Eubacterium saphenum , Filifactor alocis , Fretibacterium sp. HMT 360, Fretibacterium sp. HMT 362, Mogibacterium timidum, Peptoniphilaceae sp. HMT 113, Peptostreptococcus stomatis, Porphyromonas endodontalis, Slackia exigua, Streptococcus gordonii , Selenomonas sputigena , Treponema amylovorum , Treponema lecithinolyticum, Treponema maltophilum, Treponema medium, Treponema parvum and Treponema socranskii ) were found to be statistically significantly associated with periodontitis. Network studies should be conducted to investigate the role of these newly identified periodontitis‐associated microorganisms through interspecies interaction and host‐microbe crosstalk analyses.